Total quality versus social quality in education: an approach to the IFSP - Santos, Marcel Pereira; Santos, Cintia Almeida da Silva (Revista Hipótese, 2020)
Quality in Professional and Technological Education was discussed from two perspectives: Total Quality, from a neoliberal and entrepreneurial perspective - which comprises education as a strategic field for social, economic and cultural development and Social Quality - that understands education as a form of emancipation of the subject. It was analyzed which conception of quality the educational scenario regarding Professional and Technological Education should be linked. A relationship was made with the pedagogical proposal of the Federal Institute of São Paulo (IFSP). The methodology included the bibliographic survey and documentary analysis of the Political Pedagogical Project of the IFSP. It was addressed to Vocational and Technological Education and Integrated High School in the IFSP. It was concluded that the IFSP has a proposal with a bias in Social Quality, as it values emancipatory education.